2009
DOI: 10.2353/ajpath.2009.080620
|View full text |Cite
|
Sign up to set email alerts
|

Latent Transforming Growth Factor-β-Binding Protein-4 Regulates Transforming Growth Factor-β1 Bioavailability for Activation by Fibrogenic Lung Fibroblasts in Response to Bleomycin

Abstract: Recent evidence suggests that subsets of lung fibroblasts differentially contribute to fibrogenic progression. We have previously shown that a subset of rat lung fibroblasts with fibrogenic characteristics [Thy-1 (؊) fibroblasts] responds to stimuli (bleomycin, interleukin-4, etc) with increased latent transforming growth factor (TGF)-␤ activation, whereas non-fibro-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
40
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(41 citation statements)
references
References 57 publications
1
40
0
Order By: Relevance
“…Fibroblasts deficient for LTBP4 are impaired in their ability to activate TGF-β, consistent with a requirement of LTBP4 for normal TGF-β activation. In LTBP4-deficient fibroblasts, reexpression of LTBP4 restored TGF-β activation, and this activation depended on the presence of both the TGF-β-binding and matrix-binding domains (23).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Fibroblasts deficient for LTBP4 are impaired in their ability to activate TGF-β, consistent with a requirement of LTBP4 for normal TGF-β activation. In LTBP4-deficient fibroblasts, reexpression of LTBP4 restored TGF-β activation, and this activation depended on the presence of both the TGF-β-binding and matrix-binding domains (23).…”
Section: Discussionmentioning
confidence: 93%
“…We maintained the fibroblast cultures at confluence for 5 days, since this condition is shown to be associated with increased LTBP4 expression and deposition into the matrix (22). TGF-β signaling in this assay is dependent on the presence of intact LTBP4 (23). After exposure to TGF-β, fibroblasts from D2-Sgcg mice displayed significantly more SMAD2/3 phosphorylation than those from 129-Sgcg mice ( Figure 6A).…”
Section: Tgf-β Signaling Is Increased By Deletion Of 12 Amino Acids Imentioning
confidence: 99%
“…Thy-1(Ϫ) lung fibroblasts did not acquire Thy-1 expression with repeated passage. These established Thy-1(ϩ) and Thy-1(Ϫ) lung fibroblasts have been used in multiple published studies (18,24,27,29,41). Lung fibroblasts were cultured in F12K medium (Cellgro, Herndon, VA) containing 10% PBS.…”
Section: Methodsmentioning
confidence: 99%
“…Data from our previous studies showed that Thy-1(Ϫ) lung fibroblasts, but not Thy-1(ϩ) lung fibroblasts, activate latent TGF-␤ in response to fibrogenic stimuli (27). LTBP-4 mediates latent TGF-␤1 activation by Thy-1(Ϫ) lung fibroblasts in response to bleomycin (18). Despite these findings, the molecular mechanisms underlying Thy-1 regulation of lung fibroblast phenotype are not well understood.…”
mentioning
confidence: 96%
See 1 more Smart Citation